IL-4 Receptor α Chain Protects the Kidney Against Tubule-Interstitial Injury Induced by Albumin Overload - Peruchetti, Diogo B.; Silva-Filho, João Luiz; Silva-Aguiar, Rodrigo P.; Teixeira, Douglas E.; Takiya, Christina M.; Souza, Mariana C.; Henriques, Maria das Graças; Pinheiro, Ana Acacia S.; Caruso-Neves, Celso (Frontiers in Physiology, 2020)
Increasing evidence has highlighted the role of tubule-interstitial injury (TII) as a vital step in the pathogenesis of acute kidney injury (AKI). Incomplete repair of TII during AKI could lead to the development of chronic kidney disease. Changes in albumin endocytosis in proximal tubule epithelial cells (PTECs) is linked to the development of TII. In this context, interleukin (IL)-4 has been shown to be an important factor in modulating recovery of TII. We have studied the possible role of IL-4 in TII induced by albumin overload. A subclinical AKI model characterized by albumin overload in the proximal tubule was used, without changing glomerular function. Four groups were generated: (1) CONT, wild-type mice treated with saline; (2) BSA, wild-type mice treated with 10 g/kg/day bovine serum albumin (BSA); (3) KO, IL4Rα–/– mice treated with saline; and (4) KO + BSA, IL4Rα–/– mice treated with BSA. As reported previously, mice in the BSA group developed TII without changes in glomerular function. The following parameters were increased in the KO + BSA group compared with the BSA group: (1) tubular injury score; (2) urinary γ-glutamyltransferase; (3) CD4+ T cells, dendritic cells, macrophages, and neutrophils are associated with increases in renal IL-6, IL-17, and transforming growth factor β. A decrease in M2-subtype macrophages associated with a decrease in collagen deposition was observed. Using LLC-PK1 cells, a model of PTECs, we observed that (1) these cells express IL-4 receptor α chain associated with activation of the JAK3/STAT6 pathway; (2) IL-4 alone did not change albumin endocytosis but did reverse the inhibitory effect of higher albumin concentration. This effect was abolished by JAK3 inhibitor. A further increase in urinary protein and creatinine levels was observed in the KO + BSA group compared with the BSA group, but not compared with the CONT group. These observations indicate that IL-4 has a protective role in the development of TII induced by albumin overload that is correlated with modulation of the pro-inflammatory response. We propose that megalin-mediated albumin endocytosis in PTECs could work as a sensor, transducer, and target during the genesis of TII.